2019
DOI: 10.1177/1129729819896226
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of post-operative duplex ultrasound following arteriovenous fistula formation: A pragmatic single-centre experience

Abstract: Background: Duplex ultrasound surveillance with pre-emptive treatment of an identified stenosis is increasingly being utilised to help maintain arteriovenous fistula patency. This study aims to determine whether post-operative duplex ultrasound surveillance can improve fistula patency at 12 months and improve the proportion of ‘pre-haemodialysis’ patients commencing haemodialysis via a usable fistula. Methods: All arteriovenous fistulae formed between 1st January 2015 and 31st August 2017 in a single, tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This procedure is safe and effective immediately, which has become the standard management of AVF stenosis ( 24 ). Whether additional intervention is necessary may be related to the results of postoperative DUS ( 25 ). Postoperative DUS follow-up may become the critical strategy for maintaining the functionality of access, especially in the early 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is safe and effective immediately, which has become the standard management of AVF stenosis ( 24 ). Whether additional intervention is necessary may be related to the results of postoperative DUS ( 25 ). Postoperative DUS follow-up may become the critical strategy for maintaining the functionality of access, especially in the early 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For effective preoperative vascular evaluation, Color flow Doppler ultrasound is an important tool for vessel mapping [4,5] and postoperative vascular access surveillance [6]. Additionally, it may be used as a preoperative examination tool for planning AV fistula surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The clinical benefit and cost effectiveness of AVF surveillance regimens are a subject of debate. 1,3,[9][10][11][12] Updated guidelines from the European Renal Best Practice (ERBP) and The National Kidney Foundation Kidney Disease Outcomes Quality Initiative (KDOQI) have found that the available evidence is inconclusive to make a recommendation on AVF surveillance and they do not suggest routine surveillance of grafts. 1,12 Several volume flow rate (VFR) quantification modalities are available.…”
Section: Introductionmentioning
confidence: 99%